Agronomic Performance and Grain Yield of Low-Nitrogen-Tolerant Maize Varieties in Two Different Agro-Ecologies - Olatuyi, O.A.; Okonji, C. J.; Adewale, B. D.; Baiyeri, S. O.; Osundare, O. T. (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2024)
The soil of Ekiti State is low in nitrogen due to continuous cropping, erosion and leaching, which has led to decrease in crop yield. A possible approach to increase maize yield even in soil with low nitrogen nutrient is the use of varieties that are tolerant to soil with low nitrogen. Experiments were conducted in two locations: Ikole-Ekiti (derived savanna) and Ikere-Ekiti (tropical rainforest) in Ekiti State, Nigeria. Four low nitrogen tolerant maize varieties developed by the International Institute of Tropical Agriculture Ibadan, Nigeria were obtained; TZEE-W Pop STR C₅, TZEE-W Pop HDT C₃ STR C₅, 2017 TZEE-W HDT STR and 2016 TZEE-W Syn Pop DT STR F₂. Three rates of nitrogen fertilizer, 0 Kg N/ha, 30 kg N/ha and 60 kg N/ha were applied. The three factors experiment were laid out in split-split plot design. Days to silking, anthesis-silking interval, flag leaf, plant height and grain yield significantly (p≤0.05) varied with the location, nitrogen rates and varieties. The results indicated that 60 kg N/ha reduced the grain yield of maize compared to 30 kg N/ha which improved the grain yield of the maize varieties in the two locations (Ikole-Ekiti: 1506.04 kg/ha and Ikere-Ekiti: 952.82 kg/ha). TZEE-W Pop HDT C₃ STR C₅ significantly had the highest grain yield among the varieties in Ikole-Ekiti and Ikere-Ekiti. High nitrogen application reduced the grain yield production of the maize varieties. Thus, low nitrogen level such as 30 kg N/ha is favourable for higher grain yield of low nitrogen tolerant maize varieties.